Pop Culture in the Classroom: Associations with Student Learning Outcomes and the Underlying Psychological Mechanisms - Su Tao; Yuchen Yang (Behavioral Sciences, 2025)
As an emerging pedagogical strategy, the integration of pop culture into university classrooms has gained increasing attention. This study employs a quasi-experimental design to investigate the potential benefits and psychological mechanisms of incorporating pop culture into higher education curricula. Data were collected from 511 students across two courses and four class sections through both survey responses and in-class essay evaluations. The results indicate that students reported higher learning satisfaction with courses incorporating pop culture compared to traditional courses. However, no significant differences were observed in essay scores between the two groups. Mediation analysis revealed that the association between pop culture integration and increased satisfaction was primarily driven by student learning engagement and the perceived functionality of the case materials. Notably, for students who had not previously been exposed to the pop culture references used in class, the pattern was reversed, suggesting a potential risk of “Pop Culture Alienation”. These findings provide empirical evidence for the pedagogical value of pop culture in higher education while underscoring the need to address its differential impact on diverse student populations.